2016
DOI: 10.1016/j.apjtm.2016.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, clinical outcomes and factors influencing mortality of patients with melioidosis in southern Thailand: A 10-year retrospective study

Abstract: Melioidosis is not uncommon in southern Thailand. The mortality of patients with pneumonia, bacteremia and septic shock is relatively high. Appropriate antibiotics, initially, will improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 27 publications
15
47
0
Order By: Relevance
“…The study found that hepatic or splenic abscess and/or skin and soft tissue infection were the most common clinical profiles and the most important clinical predictors of pediatric melioidosis. A previous study on melioidosis in our hospital from 2002 to 2011 which recruited all patients aged more than 1 year found that the median (IQR) age of infection was 49 (34-58) years and the proportion of patients with hepatic abscess was 19.4% and with splenic abscess was 20.9% [3]. In the current study which enrolled only children in contrast to the all-ages study, we found similar proportions of children with hepatic abscess 29.6% (8/27) and splenic abscess 22.2% (6/27).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The study found that hepatic or splenic abscess and/or skin and soft tissue infection were the most common clinical profiles and the most important clinical predictors of pediatric melioidosis. A previous study on melioidosis in our hospital from 2002 to 2011 which recruited all patients aged more than 1 year found that the median (IQR) age of infection was 49 (34-58) years and the proportion of patients with hepatic abscess was 19.4% and with splenic abscess was 20.9% [3]. In the current study which enrolled only children in contrast to the all-ages study, we found similar proportions of children with hepatic abscess 29.6% (8/27) and splenic abscess 22.2% (6/27).…”
Section: Discussionmentioning
confidence: 94%
“…It is an important public health problem in areas in which it is endemic such as Southeast Asia and northern Australia [1,2]. Clinical presentation ranges from a localized infection, such as parotitis or skin abscess, to severe septicemia [3][4][5]. In a study from northeastern Thailand, Limmathurotsakul et al reported an estimated melioidosis mortality rate of 8.6 per 100,000 population (95% confidence interval (95% CI): 7.33-10.11), the third most common cause of death from infectious disease in northeastern Thailand, following human immunodeficiency virus/acquired immunodeficiency syndrome and tuberculosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…A male‐biased incidence was found among the neonatal melioidosis cases (68%; 15/22), similar to childhood and adult melioidosis . The odds of fatal outcome were found 3.67 times higher among male than the odds were among female neonates.…”
Section: Discussionmentioning
confidence: 99%
“…A male-biased incidence was found among the neonatal melioidosis cases (68%; 15/22), similar to childhood 3,4,19 and adult melioidosis. 14,[20][21][22] The odds of fatal outcome were found 3.67 times higher among male than the odds were among female neonates. Association of the male sex with fatal neonatal melioidosis although was not statistically significant (P = .2127), there could be an underlying biological significance given the consistently reported higher incidence in male across the age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Management is difficult as B. pseudomallei is intrinsically resistant to many antibiotics and typically treatment requires at least 2 weeks of intravenous antibiotic therapy followed by lengthy oral therapy, often with multiple antibiotics [1,5]. Despite efficacious antibiotic therapy being available, there is still significant mortality and morbidity, and there is no guarantee of clinical success, often due to severe forms of the disease [6]. Furthermore, this brings up the potential for prolonged latent disease, which represents a future problem for the individual infected.…”
Section: Introductionmentioning
confidence: 99%